Abnormal vaginal bleeding in women of reproductive age treated with edoxaban or warfarin for venous thromboembolism: a post hoc analysis of the Hokusai‐VTE study - Scheres, Luuk J. J.; Stach-Jablonski, Ksenija (BJOG)
Abnormal vaginal bleeding occurred more frequently in women treated with edoxaban than with warfarin.
Published online 2018 Jul 20
Gesehen am 13.06.2019